Reproductive effects of the psychoactive beverage ayahuasca in male Wistar rats after chronic exposure - Santos, Alana de Fátima Andrade (2017)
Ayahuasca is a psychoactive beverage used ancestrally by indigenous Amazonian tribes and, more recently, by Christian religions in Brazil and other countries. This study aimed to investigate the reproductive effects of this beverage in male Wistar rats after chronic exposure. The rats were treated by gavage every other day for 70 days at 0 (control), 1×, 2×, 4× and 8× the dose used in a religious ritual (12 animals per group), and animals euthanized on the 71st day. Compared to controls, there was a significant decrease in food consumption and body weight gain in rats from the 4× and 8× groups, and a significant increase in the brain and stomach relative weight at the 8× group. There was a significant increase in total serum testosterone, and a decrease in spermatic transit time and spermatic reserves in the epididymis caudae in the 4× group, but not in the highest dose group. No significant changes were found in the other reproductive endpoints (spermatozoid motility and morphology, total spermatozoid count and daily sperm production), and histology of testis and epididymis. This study identified a no-observed-adverse-effect-level for chronic and reproductive effects of ayahuasca in male Wistar rats at 2× the ritualistic dose, which corresponds in this study to 0.62 mg/kg bw N, N-dimethyltryptamine, 6.6 mg/kg bw harmine and 0.52 mg/kg bw harmaline. A potential toxic effect of ayahuasca in male rats was observed at the 4× dose, with a non-monotonic dose–response. Studies investigating the role of ayahuasca components in regulating testosterone levels are needed to better understand this action.